Laboratory and clinical experience with a diffractive trifocal intraocular lens sutured to an artificial iris - Mayer, Christian; Son, Hyeck Soo; Łabuz, Grzegorz; Baur, Isabella; Yildirim, Timur Mert; Auffarth, Gerd U.; Khoramnia, Ramin (Journal of refractive surgery, 2022)
PURPOSE: - - To determine in vitro, using a translational research approach before realizing the procedure in a patient with iatrogenic aphakia and partial aniridia, whether suturing a trifocal intraocular lens (IOL) to an artificial iris degrades the IOL's optical quality. - - METHODS: - - Optical quality was analyzed by measuring the modulation transfer function (MTF) at a 3-mm aperture and at 50 and 100 lp/mm spatial frequencies. The FineVision Pod F GF IOL (PhysIOL) was assessed in two powers: two +20.00 diopters (D) (20A and 20B IOLs) and two +30.00 D (30A and 30B IOLs). The IOLs' decentration in relation to the artificial iris's center was evaluated. The laboratory results provided empirical evidence in the informed consent for surgical intervention in a patient with iatrogenic aphakia and iris defect in one eye. Clinical results were measured using the parameter of corrected distance visual acuity plus a patient self-assessment of the cosmetic appearance of the operated eye. - - RESULTS: - - The 20A and 20B IOLs demonstrated a mean MTF reduction of up to 1.1%, whereas the 30A and 30B IOLs showed a decrease of up to 5.2% for both spatial frequencies. All lenses showed good centration levels. In the clinical case, the patient showed corrected distance visual acuity, distance-corrected near visual acuity, and distance-corrected intermediate visual acuity of 0.20, 0.20, and 0.22 logMAR, respectively. The patient was satisfied with the cosmetic outcome. - - CONCLUSIONS: - - There was merely a slight reduction in trifocal IOL optical quality after it was sutured to an artificial iris. Clinically, the combined implantation of the artificial iris and FineVision IOL provided good functional and cosmetic outcomes. - - [J Refract Surg. 2022;38(1):61-68.]
Gesehen am 07.09.2022